Hidden champions as a determinant of regional development: An analysis of German districts - Lena Benz; Jörn Block; Matthias Johann (ZFW - Advances in Economic Geography, 2024)
Hidden Champions (HCs) are defined as market leaders in niche markets. They represent the success of the German Mittelstand like no other group of firms. However, little is known on how HCs contribute to regional development. Given their export strength, regional embeddedness, and strong vertical integration we expect HCs to have a profound effect on regional development. Using a German dataset of 1,645 HCs located in 401 German districts, we analyze the effect of HCs on a variety of regional development dimensions. Our results show that HCs are not equally distributed across regions and influence regional development. Regions with a higher number of HCs show strong regional economic performance in terms of median income. Moreover, HC intensity affects regional unemployment and trainee rates as well as regional innovation in terms of patents. Surprisingly, we did not find an effect of regional HC intensity on regional R&D levels and GDP. We can further conclude that the effect of HCs is not limited to the particular region in which they are located but that sizable spillover effects exist. Besides its contribution to the regional development literature, our study adds to a better understanding of the HC-phenomenon. Implications for regional policy makers are discussed.
Keywords: 330; Germany; hidden champions; innovation; Mittelstand; regional development; regional performance